Efficacy and safety of glucagon‐like peptide‐1/glucagon receptor co‐agonist JNJ‐64565111 in individuals with obesity without type 2 diabetes mellitus: A randomized dose‐ranging study. Issue 2 (21st January 2021) - Alba, Maria; Yee, Jaqueline; Frustaci, Mary Ellen; Samtani, Mahesh N.; Fleck, Penny
Summary: Individuals with obesity have a heightened risk of developing serious comorbidities, and pharmacological treatments for people with obesity are limited. This phase 2 study assessed the safety and efficacy of JNJ‐64565111, a dual agonist of glucagon‐like peptide‐1 and glucagon receptors, in individuals with class II/III obesity without type 2 diabetes. In this randomized, double‐blind, placebo‐controlled and open‐label active‐controlled, parallel‐group, multicentre study, participants aged 18 to 70 years with a body mass index of 35 to 50 kg/m 2 and stable weight were randomly assigned in a 1:1:2:2:2 ratio to blinded treatment with placebo; JNJ‐64565111 (5.0, 7.4 or 10.0 mg, each with no dose escalation), or open‐label liraglutide 3.0 mg. The primary efficacy endpoint was percent change from baseline in body weight at week 26. Four‐hundred seventy four participants were randomized and 343 (72.4%) completed treatment. At week 26, placebo‐subtracted body weight changes (adjusted for multiplicity) were −6.8%, −8.1% and −10.0% for the JNJ‐64565111 5.0 mg, 7.4 mg and 10.0 mg groups, respectively, and −5.8% for the liraglutide group. Incidence of treatment‐emergent adverse events, especially nausea and vomiting, was higher in each JNJ‐64565111 treatment group compared to placebo and liraglutide. JNJ‐64565111 significantly reduced body weight in a dose‐dependent manner vs placebo but was associated with greater incidence of treatment‐emergent adverse events.